2020
DOI: 10.1590/2175-8239-jbn-2019-0183
|View full text |Cite
|
Sign up to set email alerts
|

Dietary pattern analysis among stone formers: resemblance to a DASH-style diet

Abstract: Recent epidemiological studies have shown that dietary patterns may have a more persistent impact on the risk of stone formation than single nutrients of the diet. Dietary Approaches to Stop Hypertension (DASH), a low-sodium and fruits/vegetables-rich diet, has been associated with a lower risk of nephrolithiasis, due to altered urinary biochemistry. This observational study aimed to investigate whether the dietary pattern of stone formers (SF) resembled a DASH-diet and its influence on urinary lithogenic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…Date of data collection was assumed to be 3 years before publication when authors left unanswered (n=15) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Response was not received from studies with missing SD: three reporting sodium (32)(33)(34), three reporting potassium (26,34,35), two reporting creatinine (26,35). Therefore, missing data were imputed: estimating the mean SD from studies with full data provided carried out in the same country ( )…”
Section: Data Extraction and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Date of data collection was assumed to be 3 years before publication when authors left unanswered (n=15) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Response was not received from studies with missing SD: three reporting sodium (32)(33)(34), three reporting potassium (26,34,35), two reporting creatinine (26,35). Therefore, missing data were imputed: estimating the mean SD from studies with full data provided carried out in the same country ( )…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…If the period of data collection covered more than a year, the midpoint was used. When both baseline and end-of-trial measurements were reported, only the former (n=15) (19,21,22,24,25,30,33,(37)(38)(39)(40)(41)(42)(43)(44), or the control group were included (n=4) (28,35,45,46).…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Rodrigues et al reported also that the diet of kidney stone formers showed a higher amount of protein and salt but lower calcium than in controls 1 . Probably, the higher percentage of diabetes in their group could have influenced patient’s food choices.…”
mentioning
confidence: 95%
“…Kidney stone disease is not only a pathology of the urinary tract, but it is also closely associated to metabolic abnormalities and incorrect dietary habits. Rodrigues et al 1 reported the results of an observational study about the metabolic and dietary features of a Brazilian population of kidney stone patients. They found that kidney stone formers had a higher prevalence of obesity, diabetes, and hypertension together with higher serum levels of glucose and triglycerides than non-stone formers.…”
mentioning
confidence: 99%
“…Nephrolithiasis represents a common disorder with a lifetime cumulative incidence of 5–10% and a progressively increasing prevalence worldwide [ 1 , 2 ], affecting all ages, sexes, and races, but frequently occurring between the 2nd and 4th decades of life [ 3 ]. Lithogenesis is characterized by an imbalance between the solubility and precipitation of minerals in the urine influenced by several factors, including climate, social-economic status, eating habits, obesity, genetic inheritance, and metabolic disorders [ 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. It is well established that stone formers (SF) exhibit a reduction of bone mineral density (BMD) [ 12 , 13 ], which may be exacerbated under low calcium intake [ 14 ], and histomorphometric studies have reported low bone formation and increased bone resorption [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%